Transformation of social policy in Serbia - Perišić, Natalija D. (Sociološki pregled, 2018)
In this review of the monograph “Transformation of Neoliberalism: Social Policy in Serbia (Sociological and Legal Analysis)”, the emphasis is on the inﬂuence of neoliberal mechanisms and strategies on reforms in three areas of social policy: education, social protection and employment. Tereby, the restructuring of social rights in Serbia (with respect to historical heritage) is considered, in the context of the processes of globalization, the rise of neoliberalism, and the role of domestic elites and middle layers.